DWORKIN'S CHAIN ROMANCE AND PERELMAN'S AUDITORIUM (Isagoge - Journal of Humanities and Social Sciences, 2022)
The present work aims at a theoretical approximation between the constructive interpretation of the norm proposed by Ronald Dworkin, in his notion of Law as a Novel in Chain, with structural concepts of the literary text (discourse agent, audience and context of production and circulation). Therefore, the concepts are narrowed with the help of the New Rhetoric proposed by Chaïm Perelman, with regard to the concepts of auditorium, speech and speaker, as well as in the overlap between them in the effective construction of an effective speech, in the light of epidictic. It will be concluded by the approximation of the figure of the jurist with a role close to the figure of the artist, in the reconstruction of worlds and in the interpretation of the reality of past and present times and aiming at future times.
Keywords: Theory of Law